The association of depression, impulsivity and suicidal ideation with organophosphate pesticide exposure amongst South African farm workers - Kootbodien, Tahira (Department of Public Health and Family Medicine, 2014)
The objectives were to evaluate the validity and reliability of four neurobehavioral instruments used in the study and to test three models hypothesised as possible causal pathways between OP exposure and depression, impulsive behaviour and suicidal ideation.